A sweet-tangy solution to obesity: Evaluating the efficacy and mechanisms of stingless bee honey and its potential clinical applications - Abu Bakar, Mohd Fadzelly (Elsevier, 2024)
Background: Obesity is a growing global health concern, posing significant challenges to individual well-being and healthcare systems. Conventional interventions are commonly limited and exhibit adverse effects, thus driving the exploration of alternative natural remedies. Scope and approach: This comprehensive review focuses on the potential of stingless bee honey as an anti-obesity agent. The type of honey is a less explored variant and has a less viscous-sweet and tangy taste. Stingless bees are from the Meliponini tribe and produce honey with superior diverse bioactive compound, including flavonoids, phenolic and organic acids, and unique sugars, compared to the traditional Apis species honey. The compounds demonstrated remarkable potential in combating obesity through numerous mechanisms. Key findings and conclusions: The present study summarises available data on the effects of stingless bee honey on obesity-related parameters, such as body weight, body mass index (BMI), blood pressure, lipid metabolism, metabolic syndrome markers, and gut microbiome management. Preliminary results indicated that stingless bee honey could reduce weight gain, modulate cardiometabolic variables, and regulate gut microbiota effectively, suggesting its potential in obesity prevention and management. The anti-obesity effects of stingless bee honey might be attributable to its bioactive components, such as phenolic and flavonoid phytochemicals and lowglycaemic index trehalulose. The current review also highlights the safety implications of consuming honey produced by stingless bees. Nevertheless, additional research is needed to elucidate the therapeutic potential and mechanisms of action of honey from stingless bees, especially in the context of clinical trials for anti-obesity therapies.